1998
DOI: 10.3109/03005364000000070
|View full text |Cite
|
Sign up to set email alerts
|

Use of Homeopathy in the Treatment of Tinnitus

Abstract: Tinnitus is a prevalent condition which has no practical and effective pharmacological treatment. In the absence of relief by conventional routes, sufferers are increasingly turning to 'alternative' or 'complementary' medicine. This paper reports the evaluation of a homeopathic preparation 'Tinnitus' by a double-blind, placebo-controlled clinical trial. The remedy was taken in tablet form at a homeopathic D60 potency. Perceived intensity and intrusiveness of the tinnitus was assessed at four points during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…and E.F.) for 3 inclusion criteria: ≥2 independent patient groups treated differently, randomization of patients, and reporting of tinnitus outcomes (if the study examined symptoms other than tinnitus, tinnitus results were reported separately). This yielded 147 studies ( Figure 1) for inclusion in data abstraction and analysis 5–151 …”
Section: Methodsmentioning
confidence: 99%
“…and E.F.) for 3 inclusion criteria: ≥2 independent patient groups treated differently, randomization of patients, and reporting of tinnitus outcomes (if the study examined symptoms other than tinnitus, tinnitus results were reported separately). This yielded 147 studies ( Figure 1) for inclusion in data abstraction and analysis 5–151 …”
Section: Methodsmentioning
confidence: 99%
“…In a study, despite survey results showing the preference of homeopathic preparations over placebo in 14 of 28 subjects, a variance analysis showed that neither VAS scores nor audiological measurements could provide significant improvements in tinnitus symptoms as a response to tinnitus. It could not be shown that homeopathy was more effective than the equivalent placebo in the treatment of tinnitus [52].…”
Section: Homeopathymentioning
confidence: 92%
“…Tinnitus is a common condition that lacks a practical and effective pharmacological treatment. When tinnitus cannot be overcome through traditional means, patients increasingly turn toward "alternative" or "complementary" drugs [52].…”
Section: Homeopathymentioning
confidence: 99%
“…Many good quality studies of the last 12 years have yielded negative results, for instance, concerning systematic reviews and meta-analyses [3][4][5][6][7][8][9][10][11] ; infections of the upper respiratory tract and allergic rhinitis 12,13 ; post-operative ileus 14 ; asthma 15 ; warts [16][17][18] ; pain relief and muscle soreness [19][20][21][22][23] ; treatment of adenoid vegetation 24 ; chronic headache [25][26][27][28] ; ear inflammation 29,30 ; eczema 31 ; arthritis 32,33 ; bruising 34,35 ; anxiety 36 ; "provings" (see below) with belladonna, arnica, Pulsatilla and mercury [37][38][39][40][41] and "aggravations" ("good" worsening of symptoms, said by homeopaths to precede patient recovery) 42 . Detailed comments on many of these studies are published 2,5,43 .…”
Section: Clinical Trialsmentioning
confidence: 99%